Mechanical characteristics of quasibinary eutectic composites with regard for the influence of an intercomponent interaction at the interface - Zakarian, D.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The theoretical strength of composite LaB6−ZrB2 at the eutectic point is calculated, by using the method of a priori pseudopotential. The maximum strain with regard for the influence of the component boundaries is calculated, as well as the dependence of the theoretical strength on the component concentrations.